A METHODOLOGICAL ANALYSIS OF THE USE OF ENGLISH TENSES IN “MEET ME IN ISTANBUL” BY RICHARD CHISHOLM - Tokhtakhonova, Aqidakhon; Sindorov , Lutfulla; Chekulai, Igor (Scientific practical conference, 2026)
This article examines the use of English tense forms in the literary work “Meet Me in Istanbul” by Richard Chisholm. The study analyzes how various tense forms function across different narrative contexts. Particular attention is given to the stylistic and semantic roles of present, past, and future tenses, as well as their perfect and continuous aspects, in shaping literary discourse. The article also explores the contribution of tense usage to the representation of reality, characterization, and the organization of narrative structure. The findings highlight distinctive features of English tense usage in literary texts and may serve as a useful resource for scholars, philologists, and English language educators.